Employees’ Lived Experience in Multicultural Work Environments in Governmental Organizations: A Phenomenological Study in Kermanshah Province - Hooshmand, Javad; Nazari, Kamran; Feghhi Farahmand, Naser (Digital Transformation and Administration Innovation, 2026)
Multicultural workplaces, due to their ethnic, linguistic, and religious diversity, create unique opportunities and challenges for both employees and organizations. Examining employees’ lived experiences in such environments plays an important role in improving policies, organizational interactions, and productivity. This study aimed to gain an in-depth understanding of the lived experiences of employees in governmental organizations when facing multicultural work environments in Kermanshah Province. The present research employed a qualitative method with a phenomenological approach. The research sample included 14 employees from governmental organizations in Kermanshah Province. Interviews continued until theoretical saturation was reached and were analyzed using Van Manen’s method. Six main dimensions and twenty-one components were identified, including (1) individual perception of diversity (understanding ethnic, linguistic, and religious differences, and perception of organizational justice in relation to diversity); (2) intercultural interactions (collaboration among colleagues of different ethnicities and religions, communication challenges such as language barriers, stereotypes, and misunderstandings, cultural learning, and cultural exchange); (3) experience of challenges (discrimination and social exclusion, sense of injustice, value and norm conflicts, and inequality of opportunities); (4) experience of opportunities (synergy and innovation arising from diversity, increased organizational social capital, enhanced empathy, and employee resilience); (5) organizational responses (policies and practices for managing cultural diversity, training and development of intercultural skills, and establishing supportive welfare–social infrastructures); and (6) individual and organizational outcomes (shared identity, increased or decreased job satisfaction, improvement or decline in organizational productivity, and sense of organizational belonging). This study emphasizes the importance of designing supportive policies and programs in governmental organizations to effectively manage multicultural work environments and demonstrates that a balanced interaction between individual perception, experience of challenges, and organizational responses is the key to creating positive lived experiences and higher employee productivity.